Clinical features of Tooth Avulsion Injuries in Vietnam - Tran Thi My Hanh; Tong Minh Son; Dam Ngoc Tram; Lê Long Nghia; Ha Ngoc Chieu; Le Thi Thuy Linh; Luong Minh Hang; Nguyen Ha Thu (Journal of Dental Problems and Solutions - Peertechz Publications, 2018)
Objective: The purpose of this study is to characterize the clinical features of patients with avulsed teeth. Material and methods: This cross-sectional and retrospective study examined 81 patients with avulsion injuries and 150 avulsed teeth at National Hospital of Odonto - Stomatology, Ha Noi, Viet Nam, from January 2010 to December 2016. Results: Dental avulsion was more common in males (61.90%) than in females. The age of 12 to 18 was the most frequent. Many causes including traffi c accidents (51.85%) and violence-related factors (37.04%). Avulsed teeth were often maxillary incisors (71.30%). 87.93% of avulsed teeth were intact; 61.73% of dental alveoli were not fractured; common damage to adjacent teeth is subluxation. Conclusion: Although clinical forms of avulsed teeth and local injuries are diverse, most common cases include avulsed maxillary central incisor.